A New Approach to Body Donation for Medical Education: The Silent Mentor Programme - Saw, Aik (Malaysian Orthopaedic Association, 2018)
Cadaveric dissection is an integral component of medical education. There had been concerns about negative impact on medical students exposed to deceased donors before their clinical years, but most studies reported overall positive outcome following this form of teaching. Due to reducing number of body donations in most parts of the world, many institutions are adopting alternative models especially for the teaching of gross anatomy. A new body donation programme that incorporate humanistic values in the procurement process was initiated by Tsu Chi University of Taiwan in 1996. Early observations following teaching with the so-called “silent mentors” noted less negative emotional impact on the students. With increasing number of body donation following the initiation of the silent mentor programme as reported in some regions, we will be able to continue the time-honoured cadaveric dissection for anatomy teaching, at the same time promoting humanistic values on junior doctors.